Optimization of Volume for an Automatic Feed Wagon by Graph Theory Based Modeling - S. M. Mikhailichenko; A. I. Kupreenko; Yu. G. Ivanov; E. A. Nikitin (Сельскохозяйственные машины и технологии, 2023)
Within the project of developing an automatic feed wagon, the initial task is to determine its overall parameters, which directly depend on the wagon volume. (Research purpose) To simulate the automatic feed wagon operation in order to determine the optimal volume ensuring the versatility of its use in cattle cowsheds accommodating different numbers of animals, and practicing different feeding frequency. (Materials and methods) The solution to the problem is based on the calculation of the feeding time taken by the automatic feed wagon. The time must not exceed the limit values established by zootechnical standards. To calculate the feeding time taken by an automatic feed wagon, a graph-theory-based simulation method was used, taking into account the probabilistic nature of the components of feed mixture distribution time balance. The calculations were performed in MS Excel. (Results and discussion) The paper describes the conditions for simulation and considers two options for the automatic feed wagon operation, in particular the option when one robot serves two cowsheds and the other when each cowshed is served by a separate feed wagon. (Conclusions) The second option with a separate automated feed wagon for each cowshed is proved to be more suitable. It has been obtained that in this case, the reduced movement length results in a 27.9-36.2 percent increase in productivity of the automatic feed wagon; besides there is no need to install automatic gates and build an insulated vestibule to move the robot between the cowsheds. Thus, the programming task becomes simplified. It has been found out that an automatic feed wagon having the volume of 2 cubic meters is enough to feed animals in the cowsheds sized 111.9 meters by 26.6 meters and smaller, accommodating up to 340 cows, and with a feeding frequency of 4-8 times a day.